2020
DOI: 10.1016/j.compstruc.2020.106251
|View full text |Cite
|
Sign up to set email alerts
|

A novel framework for modelling the 3D mesostructure of steel fibre reinforced concrete

Abstract: This paper presents a novel method for modelling the three-dimensional four-phase mesostructure of steel fibre reinforced concrete (SFRC) consisting of coarse aggregates, mortar, interfacial transition zone and fibres, which provides several advanced features. It enables constructing various types of short discrete fibre like straight, spiral and hooked-end fibres with one-or three-dimensional elements while configuring their sizes and orientations. A key aspect of the approach is the capability of generating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 44 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…The coarse aggregate used for pouring concrete in the project is usually irregular crushed stone. Naderi et al 74 and Sadouki et al 75 found that the aggregate shape significantly affects the performance of concrete, while existing studies mostly use random convex polygons to simulate coarse aggregates, which do not reflect the actual shape of coarse aggregates. Therefore, this article uses the equivalent convex polygon based on the actual shape of stone clasts to simulate the coarse aggregate.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…The coarse aggregate used for pouring concrete in the project is usually irregular crushed stone. Naderi et al 74 and Sadouki et al 75 found that the aggregate shape significantly affects the performance of concrete, while existing studies mostly use random convex polygons to simulate coarse aggregates, which do not reflect the actual shape of coarse aggregates. Therefore, this article uses the equivalent convex polygon based on the actual shape of stone clasts to simulate the coarse aggregate.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…Along this line, simplified approaches for the modeling of geo-microstructures have been developed in a number of research works (e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13]). In addition, more advanced and sophisticated modeling approaches have also been reported (e.g., [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]). It is however noted that, in the aforementioned studies, interest has been placed in the simulation of the coarse-scale microstructures.…”
Section: Introductionmentioning
confidence: 99%